Clinical treatment strategy and follow-up of lymphoepithelioma-like carcinoma: a retrospective study - Shilong Zhang; Yufu Lin; Zhiyong Li; Zhiming Wang; Rongkui Luo; Xiuping Zhang (Future Science OA, 2024)
Aim: To investigate the clinical features, diagnosis and treatment of lymphoepithelioma-like carcinoma (LELC).Materials & methods: The clinical data of 114 LELC patients were retrospectively analyzed.Results: Ninety-eight patients (86.0%) were Epstein-Barr virus-encoded small RNA (EBER) positive detected by situ hybridization. A 67.1% (51/76) patients had PD-L1 expression. The 5-year overall survival rate of EBER negative patients was 51.6% while the rate of positive patients was 84.8% (p = 0.015). The 5-year progression free survival rate of EBER negative patients was 40.2% while the rate of positive patients was 70.2% (p = 0.004).Conclusion: The progression of LELC is relatively slow and present a better prognosis. The occurrence of tumor is closely related to Epstein–Barr virus infection and PD-L1 is highly expressed in tumor cells.